Infrastructure Security of the Ural Regions: Assessment Technique and Diagnostic Results - Pykhov, Pavel Arkadyevich; Kashina, Tatyana Olegovna (Economy of Regions, 2015)
This article examines the infrastructure as one of the important elements of the economic system. Authors have considered the stages of formation of this concept in the scientific world, the ideas of a number of scientists on a role and place of infrastructure in the economic system are given. Short genesis of approaches to the description of infrastructure and to assignment of its functions to certain branches is created. The paper emphasized the importance of strengthening the infrastructural support to the transition of the economy to the machine mode of production. Two main methodological approaches describing the nature and content of infrastructure are allocated: branch-wise and functional. The author’’s technique of the assessment of infrastructure security of territories at the regional level is offered. A basis of this technique is the allocation of the set of special indicators which values allow to see the level of development of separate elements of infrastructure. Indicative analysis, which is the basis of the methods, allows to judge any phenomenon by comparing the current observed values with the previously accepted threshold levels. This comparison allows one to classify the observations on the scale of "norm-pre-crisis-crisis". The essential advantage of this method is the normalization of indicators, i.e. their reduction to one comparable conditional size. It allows to receive the assessment on certain blocks of indicators and a complex assessment on all set in general. Authors have allocated four basic elements of infrastructure, such as transport, communications and telecommunications, utilities and health care availability. In total, the technique includes 21 indicators. The results of approbatory calculations with the author’’s method have revealed shortcomings in the infrastructure development of the Ural region. The article is a brief analysis of the data with the accents on the individual indicators and areas.